ANALISIS GANGGUAN HUBUNG SINGKAT UNTUK SETTING DISTANCE RELAY PADA SALURAN UDARA TEGANGAN TINGGI (SUTT)70 kV ANTARA GARDU INDUK SIDERA – GARDU INDUK TALISE - Barthin Tandiling, Aprilius Petingko, Muhammad Sarjan, Yulius Salu Pirade (Foristek, 2018)
A short circuit is one of the most common types of disturbances in a power system, either short-circuit between wire to ground and short circuit between different phase wires. When the disturbance occurs, the current flowing in the transmission line leading to the center of the disturbance is very large, so it will affect the stability of the entire system, To avoid damage and large losses, the distance relay is used as the main protection in securing the transmission line. This study discusses the short-circuit currents of one ground phenomenon that occurs in the main substation of talise heads, and simulates short circuit one phase to ground using ETAP (Electric Transient and Analysis Program) 12.6.0 software. From the calculation of this research, the largest short circuit current flows occur in the type of short-circuit current disturbance of the ground phases with the disturbance distances at 25% distance of 827,84 A, disturbance distances at 50% distance of 792,97 A, disturbance distances at 75% distance of 760,29 A and short circuit current of one ground phases with distances distances at 100% distance of 729,71 A and the result of distance relay setting value for zone 1 of ZSetting-1 value is 2,672 Ω and ZSetting-0 value is 5,148 Ω, for zone 2 the value of ZSetting-1 is 4,809 Ω and ZSetting-0 value is 9,226 Ω , and for Zone 3 the ZSetting-1 value is 8.91 Ω ZSetting-0 value is 10.117 Ω.